Analisis Gaya Komunikasi Presenter Metro TV Melalui Roasting - Rifky Chrystian Pananto; Maria Delfriance None; Enjellina Br Tarigan; Florentina Perada Aran (GLOBAL SCIENTS PUBLISHER, 2025)
This study examines the communication style of Metro TV presenters through the roasting technique as an innovation in delivering information in the digital era. The roasting technique was chosen because it combines elements of social criticism with entertainment, making it appealing to audiences, especially the younger generation. This research was conducted using a qualitative approach with descriptive methods through a documentary study of Metro TV's YouTube broadcasts. The results show that the presenters use a dominant and dramatic style, characterized by assertive intonation, expressive facial expressions, and sarcastic yet intelligent language. Furthermore, it was found that two-way interaction with audiences on social media strengthens engagement and the effectiveness of the message delivered. These findings indicate that roasting is not merely entertainment, but a communication strategy capable of conveying social criticism in a communicative and easily accepted manner. The results of this study are important as a reference for media in developing a communication style that is more adaptive, creative, and relevant to the needs of today's society.